Acute Dizziness - Gurley, Kiersten L.; Edlow, Jonathan A. (Seminars in Neurology, 2019)
Dizziness is a common chief complaint with an extensive differential diagnosis that includes both benign and serious conditions. Physicians must distinguish the majority of patients who suffer from self-limiting conditions from those with serious illnesses that require acute treatment. The preferred approach to the diagnosis of an acutely dizzy patient emphasizes different aspects of the history to guide a focused physical examination, with the goal of differentiating benign peripheral vestibular conditions from dangerous posterior circulation strokes. Currently, misdiagnoses are frequent and diagnostic testing costs are high. This partly relates to use of an outdated diagnostic paradigm. This commonly used traditional approach relies on dizziness “symptom quality” or “type” (vertigo, presyncope, disequilibrium) to guide inquiry. It does not distinguish benign from dangerous causes and is inconsistent with current best evidence. A better approach categorizes patients into three groups based on timing and triggers. Each category has its own differential diagnosis and targeted bedside approach: (1) acute vestibular syndrome, where bedside physical examination differentiates vestibular neuritis from stroke; (2) spontaneous episodic vestibular syndrome, where associated symptoms help differentiate vestibular migraine from transient ischemic attack; and (3) triggered episodic vestibular syndrome, where the Dix-Hallpike and supine roll test help differentiate benign paroxysmal positional vertigo from posterior fossa structural lesions. The “timing and triggers” diagnostic approach for the acutely dizzy derives from current best evidence and offers the potential to reduce misdiagnosis while simultaneously decreasing diagnostic test overuse, unnecessary hospitalization, and incorrect treatments.
Keywords: dizziness; vertigo; diagnosis; misdiagnosis; BPPV; vestibular neuritis; nystagmus; posterior circulation stroke